Coating studies of buried pipe in soil by novel approach of electrochemical impedance spectroscopy at wide frequency domain. (May 2015) - Li, X.; Castaneda, H.
<x content-type="archive" xml:space="preserve">Abstract</x> The coating performance of buried pipe in clayey soil has been studied by electrochemical impedance spectroscopy (EIS). The results of EIS at 300 days have been analysed by electric equivalent circuit (EEC) models. The new parameters ensemble average phase (EAP) and ensemble average impedance (EAI) were introduced, obtained directly from Bode plots at a wide frequency domain in EIS data. These two parameters proved to be effective and convenient when evaluating the performance evolution of the coatings used in buried pipe in clayey soil, for both intact and defective coatings. The results indicated that the EAI parameter has a good agreement with the fitting results by EEC models and that the changes in EAP over time illustrated the three damage evolution stages of coated pipe in soil. It is concluded that EAP and EAI can be used for fast evaluation of coatings used in practical buried pipeline in soil.